Work ability as prognostic risk marker of disability pension: single-item work ability score versus multi-item work ability index - Corné AM Roelen; Willem van Rhenen; Johan W Groothoff; Jac JL van der Klink; Jos WR Twisk; Martijn W Heymans (Nordic Association of Occupational Safety and Health (NOROSH), 2014)
OBJECTIVES: Work ability predicts future disability pension (DP). A single-item work ability score (WAS) is emerging as a measure for work ability. This study compared single-item WAS with the multi-item work ability index (WAI) in its ability to identify workers at risk of DP. METHODS: This prospective cohort study comprised 11 537 male construction workers, who completed the WAI at baseline and reported DP after a mean 2.3 years of follow-up. WAS and WAI were calibrated for DP risk predictions with the Hosmer-Lemeshow (H-L) test and their ability to discriminate between high- and low-risk construction workers was investigated with the area under the receiver operating characteristic curve (AUC). RESULTS: At follow-up, 336 (3%) construction workers reported DP. Both WAS [odds ratio (OR) 0.72, 95% confidence interval (95% CI) 0.66-0.78] and WAI (OR 0.57, 95% CI 0.52-0.63) scores were associated with DP at follow-up. The WAS showed miscalibration (H-L model χ^²=10.60; df=3; P=0.01) and poorly discriminated between high- and low-risk construction workers (AUC 0.67, 95% CI 0.64-0.70). In contrast, calibration (H-L model χ_²=8.20; df=8; P=0.41) and discrimination (AUC 0.78, 95% CI 0.75-0.80) were both adequate for the WAI. CONCLUSION: Although associated with the risk of future DP, the single-item WAS poorly identified male construction workers at risk of DP. We recommend using the multi-item WAI to screen for risk of DP in occupational health practice.